Comment on the Pope's Letter - Read, Gordon F. (Canon Law Society newsletter, 2009)
Kommentar zu: Benedikt XVI., Pope Benedict XVI.'s Letter concerning the remission of the excommunication of the four Bishops consecrated by Archbishop Lefebvre vom 10.03.2009, Canon Law Society of Great Britain & Ireland. Newsletter 158/2009, 7-11.